Extraction of 10–30-Day Stable Components from a Boreal Atmosphere during ENSO Phases - Kuo Wang; Guolin Feng; Yuxing Zeng; Zhengquan Li (Discrete Dynamics in Nature and Society)
Distinguishing the predictable 10–30-day stable components (STs) in the actual atmosphere has been important in atmospheric science research. In this study, a new method for extracting 10–30-day STs was developed with the use of historical observations. We extracted and analyzed 10–30-day STs via statistical extrapolation tests. The results show that the STs are maintained uniformly at the intraseasonal time scale; the overall trends in the atmospheric motion are revealed. Comparisons between pentad-by-pentad changes in the explained variances of the 10–30-day STs under ENSO phases show that the explained variance transmission attenuation trends for El Niño and La Niña years are weaker and more continuous than those of neutral years. Data for 10–30-day STs can remain continuous and stable from one month to the next. The proposed method and results present a new means of extracting predictable STs from the atmosphere using historical data.